The Effect of DuoLingo and SPADA to Teach Listening to Students with Different Achievement Levels - Hadziq Najmuddin Purwanto; Abdurrahman Faridi; Fahrur Rozi (English Education Journal, 2022)
There are various levels of students’ achievement in English listening classrooms. Students with different achievement levels (i.e. high achieveing students and low achieveing students) respond differently towards teaching media as well. The aim of this research was to examine the difference of students’ performance, both before and after they were taught by using two English listening teaching media namely DuoLingo mobile application and SPADA (Sistem Pembelajaran Daring Indonesia) platform. As a quantitative research it employed the Experimental factorial 2 x 2 design. Students were divided into two groups based on their achievement classification. The two groups involved in this study were high achieveing students and low achieveing students, and each group were further divided into another two group to be taught with DuoLingo mobile application a for one group and with Sistem Pembelajaran Daring Indonesia platform for the other group. It was found that both Duo Lingo mobile application and Sistem Pembelajaran Daring Indonesia platform does contribute to an increase in students’ performance for both high achievers and low achievers. This research is expected to contribute as a reference for English teachers to choose teaching media to teach listening to students with different achievement levels, and also as a further research regarding media usage for teaching listening to students with different achievement levels.